A review on the recent application of dimethyl carbonate in sustainable biodiesel production. (1st June 2020) - Esan, Akintomiwa Olumide; Adeyemi, Ayodele Dorcas; Ganesan, Shangeetha
Abstract: Major environmental concerns associated with climate change due to excessive carbon dioxide emissions have mandated the utilization of non-fossil fuels for a more sustainable environment. One of the widely recognized non-fossil fuel is biodiesel which has numerous advantages over fossil fuel. Major issues arising with biodiesel production is the expensive nature of the process which has hindered its sustainability. A suitable way of maximizing the economics of the production process is to avoid glycerol production which has become of low economic value due to its being over-surplus in the chemical industry market. The use of dimethyl carbonate (DMC) makes this possible with the production of glycerol carbonate (GC) which ensures a profitable biodiesel production process. This review discusses the various ways in which DMC has been used in biodiesel production, starting from its usefulness in in-situ transesterification and extraction processes to its application in supercritical and non-supercritical transesterification processes. It also investigates the recent coupling transesterification reaction and glycerol carbonate production processes involving DMC. There is the need for a detailed technoeconomic analysis of DMC-biodiesel to validate its economic potential in terms of production cost as well as ascertaining the efficiency and quality of the DMC-biodiesel in diesel engines.